Modified hybrid median filter with local preserving for removal of low density randomvalued impulse noise in images / Muhammad Sailuddin Darus ...[et al.] - Darus, Muhammad Sailuddin; Isa, Iza Sazanita; Md Tahir, Nooritawati; Sulaiman, Siti Noraini (UiTM Press, 2018)
Random-valued impulse noise has proven to be more difficult to remove from corrupted images than standard impulsive noise due to its random nature. Because standard impulse noise filters target the whole images pixels, useful image details and information may be loss after the filtering process. To filter the corrupted pixels and preserve important image details during filtering, it is vital to introduce local preserving to the filter. In this paper, a new filter for the removal of randomvalued impulse noise in digital grayscale images is presented. The filter is made up of two different stages which is noise detection and filtering steps, in which the properties of the random-valued impulse noise and a modified hybrid median filter is used. This noise detection is based on the histogram information of the image corrupted by random-valued impulse noise to prevent the filtering of noise free image pixels. The filtering of the detected noisy pixels is performed afterwards using the modified hybrid median filter. By introducing a local preserving scheme to the modified hybrid median filter, the results obtained is shown to outperform the standard median filter as well as the modified hybrid median filter.